The impact of digitalization in the dissemination of knowledge: impact indexes and open access in the social sciences and humanities (Journal of Philosophy Culture and Political Science, 2018)
In this paper, the authors unveil the challenges that knowledge dissemination and preservation faces in the 21th-century. From the development of the printing press to the rise of the Internet, the geographies of academic knowledge seem to have remained concentrated in concrete regions of the world. This paper examines the structure of these concentrations of knowledge in the particular case of knowledge dissemination within the Social Sciences and Humanities. First the paper looks briefly into the relationship between memory preservation and the changes that the material forms of information support have suffered in recent years. Then, it goes on to explore the challenges of a globalized world economy and the impact of the publication industry and on its uneven distribution, pointing out the unbalances and deficiencies across world zones. The research also looks at issues of environmental degradation, e-waste, and digital graveyards in certain areas of the globe in an attempt to seek avenues for future responsible action. Key words: Academic publications, impact Indexes, Social Sciences and Humanities.